The Influence of Leadership Style, Compensation, and Work Environment on Turnover Intention at PT Hi-Lex Cirebon - Mohammad Abriel Alatas; Kartono (Majapahit Journal of Islamic Finance and Management, 2026)
Turnover intention is an important human resource issue in manufacturing companies because employee stability is closely related to production continuity, work discipline, and organizational performance. This study aims to examine the influence of leadership style, compensation, and work environment on turnover intention among employees of PT HI-LEX Cirebon. The study used a quantitative survey approach involving 100 employees as respondents. Data were collected through a five-point Likert-scale questionnaire and analyzed using SPSS 27. The analysis included validity testing, reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that leadership style has a positive and significant effect on turnover intention, with a significance value of 0.015. Compensation does not have a significant effect on turnover intention, with a significance value of 0.598. Work environment has a positive and significant effect on turnover intention, with a significance value of 0.029. Simultaneously, leadership style, compensation, and work environment have a significant effect on turnover intention, with a significance value of 0.000. The Adjusted R Square value of 0.169 indicates that the three independent variables explain 16.9% of the variation in turnover intention. These findings imply that PT HI-LEX Cirebon should prioritize leadership improvement and work-environment development while continuing to evaluate compensation fairness as part of a broader employee retention strategy.